Efl Teachers’ Cognition And Practices Of Educational Equity In Teaching Of Reading In China - Chen, Feifei (2023)
Educational equity (EE), seen as an important theme in the 2030 Sustainable Development Goals, relates closely to English language education. Promoting EE in the actual classroom, especially in the main reading course, is an integral part of College English language education in China. However, EFL teachers in China do not practice EE well and they often hold distorted cognition of teaching of reading. Since teachers’ practices are related to their cognition and influenced by experiential and contextual factors, it is critical to recognize the vital links among these elements. The scant literature on examining EFL teachers’ cognition and practices concerning EE in the Chinese context and the inconsistency reported in the previous studies necessitate the study. Therefore, framed by Borg’s language teacher cognition, Rawls’ theory of justice, and Guthrie et al.’s CORI framework, this study aimed to explore Chinese college EFL reading teachers’ cognitions of EE, the consistency of their cognition and practices of EE, the experiential and contextual factors that affect their practices of EE as well as to identify teachers’ equitable strategies and the way they developed them. An interpretive qualitative approach was adopted and the data from two semi-structured interviews, classroom observations, and lesson plan documents of 10 participants selected by purposive and criterion sampling were analyzed through thematic analysis. The findings revealed teachers’ cognition of EE in teaching of reading in terms of knowledge of EE, beliefs in enhancing EE, and pedagogical thinking in practicing EE was rather comprehensive.